PENGARUH METODE KARYA WISATA TERHADAP HASIL PEMBELAJARAN IPS PADA SISWA KELAS IV SD NEGERI 095 GUNUNG TUA - Nanda Wahyuni; Rahmi Seri Hanida (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The aim of this research is to investigate the effect of applying the field trip method on social studies learning outcomes in grade IV elementary schools. The Social Sciences (IPS) learning process in schools has so far placed more emphasis on mastering large volumes of material. As a result, learning becomes rigid and focused on the teacher. As a result, students do not get the opportunity to actively contribute to learning and understand what is being taught. Students' activeness in learning and understanding of the material increases. The research results show that the results of studying social studies using the field trip method have the highest score of 90 and the lowest 60 with an average of 74. Based on the explanation above, it proves that the field trip method is very appropriate and suitable for use as a learning method in elementary schools, especially in social studies lessons. The t value is 18.525 calculated > t 0.404 table or -t 0.001 calculated < -t 0.05 table then H₀ is rejected and Hₐ is accepted, so it can be concluded that there is an influence of the use of field trip strategies on the learning outcomes of class IV students at SD Negeri 095 Gunung Tua